2020
DOI: 10.1186/s12876-020-01512-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma bile acids are associated with gallbladder stones and polyps

Abstract: Background The development of gallbladder disease (GBD) is related to bile acid (BA) metabolism, and the rate of BA circulation increases the risk of biliary cancer. However, it is unclear whether patterns of circulating bile acids (BAs) change in patients with benign GBDs such as gallbladder stones and polyps. Herein, we compared and characterised plasma BA profiles in patients with cholecystolithiasis and non-neoplastic polyps with healthy controls, and explored relationships between plasma BA profiles, demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Dietary cholesterol could increase LDL-C concentrations, 41 which contributed to gallstone formation. 42,43 Patients with gallstones have a higher level of secondary bile acids, 44 which was correlated with promoting cancerogenesis. 45 An individual with higher dietary cholesterol intake has a higher risk of dyslipidemia, 40 which may bring about the imbalance between inflammatory cytokines and anti-inflammatory cytokines in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary cholesterol could increase LDL-C concentrations, 41 which contributed to gallstone formation. 42,43 Patients with gallstones have a higher level of secondary bile acids, 44 which was correlated with promoting cancerogenesis. 45 An individual with higher dietary cholesterol intake has a higher risk of dyslipidemia, 40 which may bring about the imbalance between inflammatory cytokines and anti-inflammatory cytokines in the body.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, SIBO can reduce the absorption of fat-soluble vitamins, such as vitamin D, 19 and research has shown that vitamin D deficiency may further aggravate the cholestasis, 20 thus starting a vicious cycle. In addition, the formation of GBPs may be associated with a disturbance of the bile acid pool 21 ,which is common in SIBO. Previous studies have found that compared to SIBO-negative patients, the levels of unconjugated bile acids were higher in SIBO-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish study showed that the shortage of bile acids was a major reason why bile was supersaturated with cholesterol in gallstones patients [ 34 ]. While secondary bile acids were higher in patients with gallstones compared with healthy controls [ 35 ], and higher overall concentrations of fecal bile acids with lower microbial diversity had been found in gallstones [ 36 ]. A prospective cohort study proved that the disorder of bile acids metabolism had already occurred at the beginning of the disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an increasing number of metabolomics studies have focused on the bile acids profile in gallstones, and demonstrate that the levels of some bile acids are significantly associated with the development of gallstones [19][20][21]. However, there is still lack of a consistent and comprehensive conclusion and the biological samples they detect are diverge.…”
Section: Plos Onementioning
confidence: 99%